SAT0182 Urinary T cells identify SLE patients with proliferative lupus nephritis and may be used to monitor treatment response. (23rd January 2014) - Enghard, P.; Rieder, C.; Kopetschke, K.; Klocke, J.; Humrich, J.; Undeutsch, R.; Biesen, R.; Burmester, G.-R.; Riemekasten, G.
Abstract : Background: Lupus nephritis (LN) is one of the main concerns in the treatment of patients with SLE. However there are no good laboratory markers to non-invasively detect and monitor kidney inflammation in patients with LN. We and others have previously reported that urinary CD4 T cells may serve as a biomarker for acute LN, however these existing studies are limited by their relatively small sample size. Objectives: To confirm that urinary CD4 T cells reflect lupus nephritis activity and may serve as a marker to monitor the local inflammation in the kidneys. Methods: Urine samples from 118 patients with SLE and 10 healthy controls were analyzed using flowcytometry and correlated with the disease activity (SLEDAI). 24 SLE patients were analyzed at the same time point of receiving a kidney biopsy. Results: In patients with renal involvement the amount of urinary CD4 T cells correlated closely with the disease activity (SLEDAI), while patients without renal involvement showed only marginal amounts of urinary T cells even during lupus flares. Healthy controls showed no urinary T cells. All patients with biopsy demonstrated proliferative LN showed highly elevated amounts of urinary CD4 T cells, while some patients with class V nephritis presented normal amounts of urinary T cells. Under treatment for acute LN one patient group quickly normalized the amount of urinary CD4 T cells while others showed a persistence of elevated urinary CD4 T cells counts. The latter patient group had a significantly higher disease activity 6 month after induction of treatment compared to the patients with normalized urinary CD4 T cells, indicating that urinary T cell count reflect treatment response. Conclusions: Elevated numbers of urinary CD4 T cells reliably identify SLE patients with proliferative LN. Furthermore the amount of urinary CD4 T cells under treatment seems to reflect treatment response. We consequently propose that urinary CD4 T cells can be used to screen for proliferative LN and to monitor the LN activity under treatment. Disclosure of Interest: None Declared